Departments of Urban of regional Planning of Saudi Universities and The Consistency of Their Graduates with Saudi Labor Market - Abdulkareem Alhowish (University of Science and Technology, Yemen, 2011)
Departments of Urban of regional Planning of Saudi Universities and The Consistency of Their Graduates with Saudi Labor Market  Abstract:  The issue of alignment between the outputs of the higher education system and the requirements of socio-economic development and the needs of Saudi labor market is one of the main development issues in Saudi Arabia, this is because, Saudi higher education system plays a critical role in human resource development by raising the efficiency of universities outputs and quality assurance, which in turn, generate a high-level professionalized persons to meet the needs of national development needs and the requirements of Saudi labor market needs. In order to evaluate the outputs of these planning departments with Saudi market needs, the researcher selected the graduated Students of planning program at University of Dammam during the last four years (2006, 2007, 2008 and 2009). The data analysis showed that, despite the fact that most department' graduates got their jobs within the first year of graduatation, their current jobs, however, does not fit with the nature of their Planning professionality. The investigation also revealed that, most of theoretical courses in the planning department do not increase the knowledge of the graduates in their current works. The study also emphasized the importance of re-evaluation of planning departments curriculums and updated their courses (theoretical and practical) to meet the needs and requirements of Saudi national development plans as well as market needs. At the end of the study, the researcher recommended a number of recommendations that would increase the competitive advantage of planning departments in Saudi labor market and improve the degrees of alignment and harmony between planning departments' outputs and Saudi market needs.